Effect of unusual weather on cereal crop production and household food security - Regmi, Hem R. (Journal of Agriculture and Environment, 2007)
For the third consecutive year, drought conditions have been severely affecting agricultural production in Nepal and in some cases turning traditionally surplus production areas into deficit ones. In addition to the heavily drought affected Mid- and Far-Western Regions, flood exacerbated by hailstones and crop diseases in various VDCs caused extensive crop loss. Drought particularly affected the traditionally food surplus areas of the Eastern Terai, particularly Siraha, Saptari and Dhanusha which reported a decline in paddy production of about 30%. A total of 109,855 hectares of paddy land (7.09%) remained fallow in 2006/07 as farmers were unable to plant due to drought. In addition, yields were lower by almost 6%. Paddy crop production consequently declined by 12.5 % compared to last year. The total food grain shortfall for the year 2006/07 has been calculated at 187,748 Mt assuming favorable weather conditions for the winter crop wheat and barley. The Journal of AGRICLUTURE AND ENVIRONMENT Vol. 8, 2007, pp. 20-29